The impact of kindergarten curricula on developing children's energies, abilities, motivation, and positive attitudes towards learning. - حمز, ا.د. سكينة كامل; Al-Harbi, Prof.Dr.Hudhaifa Ibrahim (Sulaimani Journal for Humanities, 2026)
The Impact of Kindergarten Curricula on Developing Children's Abilities, Motivations, and Positive Attitudes Towards Learning Childhood is considered one of the most important stages of development, representing the cornerstone in building and shaping an individual's personality. During this stage, the path of social, emotional, intellectual, and physical development is determined, and individuals acquire many concepts, skills, and attitudes. Therefore, most countries give this stage considerable attention through organized educational, media, developmental, and preventative programs designed to prepare children well. Among these programs is the establishment of kindergartens to develop children's abilities, motivations, and positive attitudes, leading to greater achievement, success, and well-being. The design of kindergarten curricula must consider educational values, which are ethical standards prevalent in educational institutions. These values are embraced by individuals in light of their beliefs and culture, encompassing both fixed principles and evolving values that keep pace with life and society. They guide children's behavior and positively regulate their actions according to priorities they define. These priorities may be explicit or implicit, understood intellectually, felt emotionally, and translated into practical actions in their lives. Most Arab countries suffer from a lack of attention to curricula that cater to preschool children (kindergarten), as their educational systems prioritize formal education and do not provide sufficient support for early childhood education. Therefore, this study aimed to evaluate kindergarten curricula and their impact on developing children's abilities, motivation, and positive attitudes towards learning. The study was conducted using a descriptive survey methodology, with a sample of 63 kindergarten teachers. The results led to the conclusion that: 1- Kindergarten curricula do not consider children's needs and do not contribute to improving most of their educational values. In light of this, the following recommendations were made: 1- Developing modern educational curricula based on scientific principles that consider children's needs and contribute to improving their future by developing their abilities, motivation, and positive attitudes towards learning.